Control System as a Service : Standardizing Service Model and Pricing Principles - Genas, Kasper Julius (My University, 2021)
The service business has aided manufacturers to supplement their new equipment sales across many fields of businesses. The service business has proven to generate steady portions of total revenues, but even larger percentual portion of total profits. Since customers have the tendency to focus more and more on their core competencies and capabilities, services have grown stead-ily day in and out. Not many studies have been made about the potential that a control system as a service can provide to a company. Through market saturation and globally competitive markets, companies meet the challenges to operate effectively in the service business, have a standardized way of working and to price their services optimally. In this master’s thesis I will explain how services and service portfolio can be standardized and what pricing principles are to be considered for them. First, the servitization as a trend in an industrial context is reviewed along with service strategies and service orientation. Also, the pricing contexts around services and the value aspect of it are reviewed. Lastly, the literature review highlights cloud services with a comparison to traditional IT services. Next, I will study how the offerings can be readjusted to offer control systems as a service with the help of cloud services and what costs to take into considerations, and how the pricing of the service could include. By comparing a traditional model and a service model, the total cost of ownership during the lifecycle has different phases. The total cost of ownership is calculated to be less for a traditional model during one traditional lifecycle. However, as a new lifecycle is initialized with a lot of in-vestment costs for software and hardware, thereby making the service model is yet again cheaper for the next couple of years. Consequently, the comparison between the models is dependent on the customer preferences and their IT strategy; the level of outsourcing it wants to practice, what cost structure it wants to pursue, and how much predictability it can have for the future, as a traditional model is not as scalable as a service model.

Palveluliiketoiminta on auttanut yrityksiä täydentämään uusien tuotetarjontaansa monilla liike-toiminta-alueilla. Palveluliiketoiminnan on osoitettu tuottavan tasaista, mutta usein jopa muuta liiketoimintaa suurempaa kokonaistuottoa yritysten tuloksista. Asiakkaiden keskittyminen ydin-toimintaansa on kasvattanut muiden osa-alueiden ulkoistamista. Automaatiojärjestelmien tuottamista palveluna ei juurikaan löydy tutkimustuloksia. Markkinoi-den kyllästymisen sekä maailmanlaajuisen kilpailun vuoksi palveluliiketoiminnalla haetaan opti-maalisia malleja kilpailuun ja uusiin ydinkyvykkyyksiin. Tässä tutkielmassa tutkitaan, miten palvelut ja palveluportfolio voidaan standardoida ja mitä hinnoitteluperiaatteita kohdeyritys voisi tarjonnassaan hyödyntää. Ensiksi tarkastellaan palve-lullistamista trendinä teollisessa kontekstissa yhdessä kanssa. Myös palvelujen hinnoittelua ja sen arvoa tarkastellaan. Lopuksi kirjallisuuskatsauksessa korostetaan pilvipalveluja verrattuna perinteisiin IT-ratkaisuihin. Seuraavaksi tutkin, kuinka nykyinen tarjontamalli voidaan muokata tarjoamaan automaatiojär-jestelmää palveluna pilvipalvelujen avulla. Myös kustannusrakennemuutokset sekä palveluhin-noittelu ja sen tulevat menetelmät otetaan huomioon. Vertaamalla perinteistä mallia ja palvelumallia, kokonaiskustannuksilla elinkaaren aikana on eri vaiheita. Perinteisen mallin kokonaiskustannusten lasketaan olevan pienemmät yhden järjestel-män perinteisen elinkaaren aikana. Sen sijaan, heti uuden elinkaaren alkaessa, kohdistuu asiak-kaalle paljon ohjelmistojen ja laitteistojen investointikustannuksia, jolloin palvelumallin kustan-nusrakenteen arvioidaan muodostuvan kustannusnäkökulmasta asiakkaalle muutamaksi vuo-deksi edullisemmaksi. Näin ollen, mallien vertailu riippuu asiakkaan mieltymyksistä ja heidän IT-strategiastaan; kuinka paljon ulkoistamista asiakas haluaa järjestelmälleen ja minkälaista kustannusrakennetta se suo-sii liiketoiminnassaan. Myös ennustettavuus on järjestelmäkontekstissa merkitsevää, sillä palve-lumallin skaalautuvuus tuo paljon etuja perinteisiin investointiprojekteihin verrattuna.
Keywords: pricing; services; business models; control systems; service design; Software as a Service; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management